Reform in a Limbo: The Politics and Politicization of Reforms in Nigeria’s Petroleum Sector - Nwozor, Agaptus; Olanrewaju, John Shola; Adedire, Solomon Adebayo; Lawal, Ejalonibu Ebenezer (International Journal of Energy Economics and Policy, 2020)
Nigeria has been on a long-winding journey to reform its petroleum sector with no end in sight. The first version of the reform bill, the petroleum industry bill (PIB) was sent to the National Assembly in 2008. The sustained opposition to the PIB from both indigenous and international oil companies as well as other stakeholders led to the decision, in 2016, to balkanize it into four bills, with each bill focusing on an aspect of the reform. The first of the tripartite bills, the petroleum industry governance bill (PIGB) was passed by both chambers of Nigeria’s National Assembly and transmitted to the president for assent. The president declined assent, thus deepening the uncertainty that characterizes the sector. Drawing data from primary and secondary sources, the paper evaluates the trajectory of Nigeria’s petroleum sector reform, including the long delay and its impact on the sector. It finds that the delay in passing the reform bills has negatively rubbed off on the country as it has stymied growth and closed off new investments. The paper advocates the depoliticization of the reform agenda in order to reposition the country’s petroleum sector for national development. Keywords: Petroleum Sector Reform, Petroleum Industry Governance Bill, national development, Nigeria JEL Classifications: P28, P48, Q35, Q38, Q48 DOI: https://doi.org/10.32479/ijeep.9085